Sexual Psychoeducation to Build Awareness and Knowledge among Elementary School Students - Wijayanti, Sheila; Kamal, Robri Fauzan; Agustin, Citra Tri; Al Majid, Dede Syifa Humaira; Arrifa, Ridhwa Muna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Cases of sexual violence against children in Indonesia continue to increase; the targets are children, who are still vulnerable because they are considered weak and dependent on adults. Lack of knowledge about sexual violence is also the reason they become victims of violence and sexual harassment. In Bogor Regency, 173 cases of sexual violence against children were reported. The violence that occurred included verbal, psychological, and physical violence, with some of the most severe cases causing broken bones. The goal is to reduce sexual violence by providing knowledge about body anatomy, touch limits, and how to prevent sexual harassment. This sexual psychoeducation is carried out using the presentation method. There are three stages carried out, namely the preparation stage, the implementation stage, and the evaluation stage. The results of this activity show that there has been an increase in awareness, in grade 5 of elementary school; there are 15 male and 16 female students. Before this activity, only 14% of male students (2 children) and 16% of female students (3 children) knew a little about it. However, this activity increased to 94% of male students (14 children), and 100% of female students (16 children). Then, in grade 6 of elementary school, there are 30 male and 24 female students. Before this activity, only 50% of male students (15 children) and 60% of female students (14 children) knew a little about it. However, this activity increased to 98% of male students (29 children), and 100% of female students (24 children). So, the students can recognize the anatomy of the reproductive organs and know about sex education and efforts to prevent sexual harassment.